Digital Transformation in Education: The Development and Implementation of E-Learning in The World of Education - Hasan Mubarok (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
E-learning has rapidly evolved from a purely computer-based learning tool to an internet-based learning solution, much needed in today's modern era. This article describes the historical evolution of e-learning, its application in schools and universities, and the proposed implementation at Wiralodra University. This study also identifies the advantages and disadvantages of experiential e-learning, both on-site and in-class, through qualitative descriptive analysis. The research shows that while e-learning offers learning flexibility, it still faces challenges such as limited infrastructure and student motivation. The article concludes with suggestions for improving e-learning systems to support educational success at various levels.